2010
DOI: 10.1159/000314548
|View full text |Cite
|
Sign up to set email alerts
|

Association between Depression Symptoms with Inflammation and Cardiovascular Risk Factors in Patients Undergoing Peritoneal Dialysis

Abstract: Despite medical progress, high morbidity and mortality rates, due primarily to cardiovascular diseases, have persisted in patients with end-stage renal disease (ESRD). Recently, nontraditional risk factors, such as inflammation and malnutrition, have been emphasized in the development or progression of atherosclerosis in ESRD patients. Depression, the most common psychological problem in the ESRD population, is also known to be associated with inflammation and malnutrition, suggesting a possible link between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(57 citation statements)
references
References 93 publications
1
56
0
Order By: Relevance
“…27 Also, Ko et al found that hsCRP significantly affected BDI score in CAPD patients, suggesting a strong association between inflammation and depression. 28 In another study using The Hamilton Depression Scale (HAMD), serum CRP closely correlated with depression score in CAPD patients. 29 However, other studies could not demonstrate such a relationship between CRP and inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…27 Also, Ko et al found that hsCRP significantly affected BDI score in CAPD patients, suggesting a strong association between inflammation and depression. 28 In another study using The Hamilton Depression Scale (HAMD), serum CRP closely correlated with depression score in CAPD patients. 29 However, other studies could not demonstrate such a relationship between CRP and inflammation.…”
Section: Discussionmentioning
confidence: 96%
“…32,33 In peritoneal dialysis (PD) patients, depression was strongly related to inflammation, malnutrition, and multiple cardiovascular risk factors, suggesting that depression is an integral part of the MIA syndrome. 34 Indeed the state of depression associates with activation of proinflammatory cytokines, and patients on maintenance HD with symptoms of depression were more likely to have high levels of serum IL-6, higher prevalence of comorbidities, higher serum total cholesterol, and lower s-albumin levels. 35 In depressed HD patients, sertraline, a selective serotonin reuptake inhibitor antidepressant, was found to have antiinflammatory effects in addition to improving depression symptoms in almost half of the HD patients.…”
Section: General Lifestyle Modifications That May Have Anti-inflammatmentioning
confidence: 99%
“…Disease-specific factors that have been found to be associated with depression include the characteristics of dialysis received [11][12][13][14], dialysis adequacy [15], kidney disease [16], restless leg syndrome [17], as well as markers of creatinine, haemoglobin and serum albumin [15,18,19]. With respect to patient status, physical functioning [20,21], exercise fitness [22,23], cytokines [18,24,25], disease comorbidity [19], nutrition [15,26], sleep problems [27], and fatigue [28] have all been linked to depression.…”
Section: Introductionmentioning
confidence: 99%